The Magazine “The Masyats Aghavni’’ on Deprivation of Pope Pius IX of His Secular Power - Movsisyan, Feliqs (History and Culture, 2021)
The Italian national-liberation movement found a warm response in the magazine “The Masyats Aghavni’’ issued in Theodosia in 1860-1865. The magazine represented the Armenian-national conservative current. In addition to some issues related to the Italian national movement, the magazine also touched upon the deprivation of Pope Pius IX (Pope of Rome) of his secular power. Archimandrite Gabriel Aivazovsky, the editor of the magazine, observed the demand of the freedom-loving Italians from religious ideology and political unification point of view. He touched upon thas issue in his articles entitled “The spiritual and secular power of Popes of Rome”. • Ayvazovsky considered inadmissible actions of Pope Pius IX and his cardinals who made great efforts and exerted pressure upon the believers to maintain the secular power of the High Priest. In his understanding, the supporters of the Papacy made a huge mistake insisting on the fact that the demand to deprive the Pope of his secular power was a real danger to his spiritual power. G. Ayvazovsky countervailed the supporters of the Pope, who were of the opinion that the Popes’ power was divine given to the Church of Jesus, therefore was a limitless spiritual an secular power. The editor of “The Masyats aghavni” refuted that approach and, quoting The Gospel, stated that Jesus Christ didn’t have any secular power and didn’t consider himself a king. He was the base of the Church, Head, Supreme Priest, Pastor and the Lord. The Creator didn’t appoint any of his apostles a Church head and granted them only a spiritual power. Thus, Ayvazovsky stated that all the Popes of Rome who considered themselves vicars of the Lord in the secular life and successors of St. Peter the Apostle, might have only a spiritual power. The editor of “The Masyats Aghavni” thought that the secular power of Pope Pius IX was a serious obstacle to the liquidation of the political separation of the Italian states. In his understanding, the Italians’ age-long dream to have a united kingdom would be realized only when Pius IX renounced his secular power. Only then the City of Rome would join the Italian Kingdom and become the capital of the whole state. The editor of the magazine “The Masyats Aghavni’’ in his publications consistently asserted that the freedom-loving Italians would be united sooner or later and their declared Italian Kingdom would certainly become one of the European advanced countries. Գ. Այվազովսկին անընդունելի է համարում Պիուս IX պապի և նրա կարդինալների գործողությունները, ովքեր ջանքեր էին գործադրում և ճնշումներ իրականացնում հավատացյալ ժողովրդի շրջանում՝ Հռոմի Քահանայապետի աշխարհիկ իշխանությունը պահպանելու նպատակով: Նրա համոզմամբ՝ պապականության կողմնակիցները մեծագույն սխալ են թույլ տալիս՝ պնդելով, թե Պապին աշխարհիկ իշխանությունից զրկելու պահանջը վնասում է նրա հոգևոր իշխանությանը: Գ. Այվազովսկին հակադրվում է Պապի աշխարհիկ իշխանության կողմնակիցներին, որոնց համոզմամբ պապերի իշխանությունն աստվածային է, ի վերուստ տրված Քրիստոսի եկեղեցուն, ուստի անսահման հոգևոր ու աշխարհիկ իշխանություն է: «Մասյաց աղավնու» խմբագիրը հերքում է այս մոտեցումը, և վկայակոչելով Ավետարանները, նշում, որ Հիսուս Քրիստոսը երկրային կյանքում փոխանորդ չուներ և իրեն թագավոր չէր համարում: Նա հանդիսանում էր եկեղեցու հիմքը, գլուխը, քահանայապետը, հովվապետը և տերը: Աստված առաքյալներից որևէ մեկին չէր կարգել եկեղեցու գլուխ և շնորհել էր միայն հոգևոր իշխանության և ոչ թե աշխարհիկ: Հետևաբար, եզրակացնում է Գ. Այվազովսկին, Հռոմի պապերը, ովքեր իրենց համարում են Աստծո փոխանորդը երկրային կյանքում և Պետրոս առաքյալի հաջորդը, կարող են ունենալ միայն հոգևոր իշխանություն: «Մասյաց աղավնու» խմբագիրը գտնում էր, որ Պիուս IX պապի աշխարհիկ իշխանությունը լուրջ խոչընդոտ է իտալական պետությունների քաղաքական մասնատվածությունը վերացնելու հարցում: Նրա կարծիքով միասնական իտալական թագավորություն ունենալու իտալացիների դարավոր բաղձանքը միայն այն ժամանակ կիրականանա, եթե Պիուս IX-ը հրաժարվի իր աշխարհիկ իշխանությունից, որը կմիանա իտալական թագավորությանը, իսկ Հռոմը կդառնա պետության մայրաքաղաքը: